The median time to develop recurrent tuberculosis at a tertiary hospital in Kota Bharu, Kelantan, Malaysia - Myat Moe Thwe, Aung; Mainul, Haque; Nyi Nyi, Naing (Open Science Publishers LLP Inc., 2016)
This study has the intention to determine the median time to develop recurrent tuberculosis [TB] in TB patients attending the Chest Clinic at Hospital Raja Perempuan Zainab II [HRPZ II], Kelantan, Malaysia. Records of 114 recurrent TB patients from 1/1/2003-31/12/2009 were analyzed. Kaplan-Meier analysis was used to examine the median time for recurrence of TB. The overall median time to develop TB recurrence in registered TB recurrent patients was six months [95%CI: 4.58, 7.42] after the previous episode. It was found that recipients of Streptomycin (S), Isoniazid (H) and Rifampicin (R) twice weekly (S2H2R2) drug regimen [p=0.026] or daily HR drug regimen [p=0.049] during the continuation phase took a longer duration to develop recurrent TB than nonrecipients of these medicines by Kaplan-Meier analysis. Moreover, there also existed a significant time difference [P = 0.006] between the defaulters and non-defaulters of treatment to develop recurrent TB. Patients should take the complete course of therapy, to reduce recurrent TB infection. The drug regimens must contain the two most potent first line drugs Isoniazid [H] and Rifampicin [R] during the continuation phase.